Audit Internal (Kas dan Teller ) pada Lembaga Keuangan Perbankan - Najihah, Wilda ‘Ainun; Siswadi, Siswadi (Al-Maqashid: Journal of Economics and Islamic Business, 2024)
Internal audit is an important procedure performed to assess internal controls in financial institutions, particularly in cash management and tellers. The purpose of this audit is to provide protection to the bank's financial assets and ensure that an effective supervisory system is in place. In this study, the authors evaluated the effectiveness of internal audit in detecting and preventing fraud, as well as ensuring compliance with applicable regulations. The methods used include qualitative and quantitative analysis to collect relevant data and support the research findings. Systematic implementation of internal audit can improve the security and reliability of bank operations. Internal auditors play an important role in identifying risks and providing significant improvement recommendations. This research also emphasizes the importance of training for auditors to improve their ability to perform their duties, thus adding value to the organization. Thus, internal audit serves not only as a control tool, but also as an important line of defense in maintaining the integrity of bank reports and operations.